Manajemen Inovasi Dalam Pelaksanaan Sertifikasi Pembimbing Manasik Haji Profesional - gina, gina fitriyani; Nase, Nase; Hilman, Fathin Anjani (Mabrur: Academic Journal of Hajj and Umra, 2024)
This study aims to determine innovation design, communication channels, implementation and participant acceptance by focusing on data collection through qualitative descriptive methods. The results showed that innovation management, namely the diffusion of innovation in the implementation of professional Hajj ritual counselor certification activities of the Faculty of Da'wah and Communication of UIN Sunan Gunung Djati Bandung Batch XXVIII, was successful. This can be seen from the enthusiasm of participants from various regions, including outside West Java, and good cooperation from the organizers, which are key factors in the successful introduction of innovations in these activities. The innovation design applied includes the use of barcode absent media, the provision of manasik props, the existence of a resume assessment system, appreciation of participants, developing curriculum according to needs.